Konsep Ta’dib sebagai Landasan Filosofis Pendidikan Islam - Bilqis Mutiara Ramadhani; Lubna Shofiyatul 'Aini; Widadatul Ngulia (Jurnal Teologi Islam, 2026)
This study aims to examine the concept of ta'dib as a philosophical foundation in Islamic education and its importance in addressing today's educational challenges. The method used is a descriptive qualitative approach through a literature review of various relevant references. The results show that ta'dib places adab (ethics) at the center of education in shaping the whole person, encompassing intellectual, moral, spiritual, and social aspects. Unlike ta'lim (Islamic study), which focuses on the transmission of knowledge, and tarbiyah (Islamic education), which emphasizes the development of potential, ta'dib is more directed at the formation of morals and a sense of responsibility towards knowledge. In the era of globalization, ta'dib plays a crucial role in addressing the decline in students' morals. Its implementation is carried out through role models, habituation, the integration of adab values ​​into learning, and collaboration across various educational environments. Thus, ta'dib is an effective approach in shaping a generation that is both knowledgeable and character-driven.